Scaling the heights: the background and development of a novel remote highwall scaling machine for use at the Savage River Mine - Anderson, MS; Johnson, C (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Savage River Mine is located in the rugged northwest of Tasmania and provides high quality Magnetite ore for pelletising. The mine is in a high rainfall area and is currently over 400 m deep with an inter-ramp slope angle of over 62°, 30 m high batter faces and 12 m wide catch benches. An unfavourable joint set dipping into the pit at around 45° frequently results in poor crest retention and loss of access along the benches. The high rainfall and life-of-mine dilation have resulted in recent rockfalls from this wall ranging from 5 t to 10,000 t. While these rockfalls have been retained over a number of benches, the resulting rill often fills the catch berms, increasing the likelihood that any subsequent rockfall in this area will reach the work area below. To address this risk a remotely controlled scaling machine has been developed as a joint project between Grange Resources and Jayben Group, Australia. It is remotely controlled and capable of descending approximately 90 m over a vertical face. This provides access to remediate unstable sections of batter and to clear failed rill material from otherwise inaccessible benches to re-establish catch capacity. The machine uses world first, real time 3D image processing technology to provide the operator and Geotechnical Engineers advanced mapping and structural data and the ability to accurately place scaling tools to best effect. Preliminary testing of the prototype has been successful, demonstrating excellent stability on even vertical batters but hi-lighted the need to further improve the wireless communication system and some hydraulic systems to address issues identified during testing.
Keywords: batter scaling machine